MST4 negatively regulates type I interferons production via targeting MAVS-mediated pathway - Wei Liu; Zhenling Ma; Yaru Wu; Cui Yuan; Yanyan Zhang; Zeyang Liang; Yu Yang; Wenwen Zhang; Pengtao Jiao (Cell Communication and Signaling, 2022)
Abstract Background Cytosolic RNA sensing can elicit immune responses against viral pathogens. However, antiviral responses must be tightly regulated to avoid the uncontrolled production of type I interferons (IFN) that might have deleterious effects on the host. Upon bacterial infection, the germinal center kinase MST4 can directly phosphorylate the adaptor TRAF6 to limit the inflammatory responses, thereby avoiding the damage caused by excessive immune activation. However, the molecular mechanism of how MST4 regulates virus-mediated type I IFN production remains unknown. Methods The expression levels of IFN-β, IFIT1, and IFIT2 mRNA were determined by RT-PCR. The expression levels of p-IRF3, IRF3, RIG-I, MAVS, and MST4 proteins were determined by Western blot. The effect of secreted level of IFN-β was measured by ELISA. The relationship between MST4 and MAVS was investigated by immunofluorescence staining and coimmunoprecipitation. Results In this study, we reported that MST4 can act as a negative regulator of type I IFN production. Ectopic expression of MST4 suppressed the Poly (I:C) (polyino-sinic-polycytidylic acid)- and Sendai virus (SeV)-triggered production of type I IFN, while the knockdown of MST4 enhanced the production of type I IFN. Mechanistically, upon SeV infection, the MST4 competed with TRAF3 to bind to the 360–540 domain of MAVS, thereby inhibiting the TRAF3/MAVS association. Additionally, MST4 facilitated the interaction between the E3 ubiquitin ligase Smurf1 and MAVS. This promoted the K48-linked ubiquitination of MAVS, thereby accelerating the ubiquitin-mediated proteasome degradation of MAVS. Conclusions Our findings showed that MST4 acted as a crucial negative regulator of RLR-mediated type I IFN production. Video Abstract